MECHANISMS OF PROVIDING THE STATE SYSTEM OF BALANCE OF THE REGIONAL BUILDING COMPLEX - Ovsak , Ivan (Theory and Practice of Public Administration, 2019)
It is noted that the most time-consuming and responsible stage of economic analysis is information. It depends on the reliability of the results of the analysis. In the case of scientific innovations and when proposing new economic indicators, it is difficult to gather primary information because of the lack of information base. In this regard, the practical implementation of economic research requires the definition of this base and the provision of primary information in the coordinating bodies of the issues considered, which, in our view, should become the regional Ministry of Regional Development, Construction and Housing and Communal Services of Ukraine. To ensure the calculation of the level of balance of the regional building complex and develop a strategy of state regulation of the balance of the regional building complex, the enterprises of this complex should submit quarterly to the Ministry of Regional Development, Construction and Housing and Communal Services of Ukraine information on a special form necessary to calculate the coefficients of nomenclature . Note that in analyzing the level of development of any economic phenomenon as a basis of comparison, either planned targets or the level of development of previous years (the base period) were taken. This approach can be taken as the basis of analysis when analyzing the level of development of one construction company. Since we are talking about an analysis of the level of development and balance of a regional construction complex consisting of many enterprises, we should take as the basis of analysis a comparison of the parameters of construction enterprises with the best achievements of individual enterprises, which provides a real analysis of the level of development. This analysis is perspective-oriented and provides a real picture of managing the development of individual enterprises, as well as contributes to the development of more realistic decisions of state bodies to regulate the level of balance of the environment of the regional construction complex. It is known that improving the level of balance of a regional construction complex depends on both the state bodies and the enterprises themselves. In this regard, in the development of strategic decisions for the development of enterprises before the leadership of the construction company are put fundamentally new tasks. Strengthening of market relations, gradual and steady formation of the market of construction products on a national and regional scale, the rate of entry into the system of the world market provides interrelation of the general goals of development of a building complex with measures of a specific character, ensuring achievement of these goals, at certain moments of time. Hence, the strategic orientation of the state regulation of construction production in its external current manifestation. This corresponds to the creation and development of forms of state regulation, on a programmatic and targeted basis, capable of creating a long-lasting “goal-to-west” link throughout the building complex and in each of its primary links. In this aspect, it is especially important to prioritize the development goals of the building complex, which are related to demand-side orientation, with increasing production efficiency and social development of the team. This requirement is met by carrying out a complex of research and analytical work that allows to specify the goals - means, tasks and conditions of their solution. Methodologically, they are based on the logic of scientific thinking, which reflects the degree of influence of economic, logistical and social factors on the formulation of the goal.